Kajian Karya 'Hama Memberkati' dengan Teori Kematian Metanarasi - Zefanya Silva (JURNAL RUPA, 2020)
Postmodern is an era after the Modern Era that is marked with some amount of transformations in science, literature, and arts. Every work of art, by many ways, must have contained some postmodern concepts. This writings will specifically talk about Natasha Tontey’s work titled ‘Pest to Power’ and will uncover every postmodern concepts and theories that are used in the artwork. This research will use qualitative methods with data from books, journals, magazines, and articles from the internet that contain postmodern concepts and the work ‘Pest to Power’. In conclusion, this research shows that ‘Pest to Power’ adopts the death of metanarratives concept as the artwork’s base and it expresses rejection towards absolute anthropocentrism. ‘Pest to Power’ also uses camp and simulacra concepts.